Clinical, Subclinical Characteristics, Treatment Results of COVID-19 patients in Dong Thap - Tuan Son, Nguyen; Duy Anh, Dao; Thi Nhung, Le; Lan, Hoang; Huu Son, Nguyen; Thi Ngan Giang, Nong; Hoang Miai Phuong, Cu; Thi Phuong Dung, Banh; Thi Ngoc Anh, Tran; Le Phuong, Vu; Van Dem, Pham; Hung, Le; et al. (VNU Journal of Science: Medical and Pharmaceutical Sciences; Vol 38 No 1, 2022)
A prospective descriptive study was conducted from August 2021 to September 2021 to describe the clinical and subclinical characteristics of COVID-19 patients at the field hospital of Dong Thap Community College. The study collected epidemiological data of 240 subjects. The results indicated that the male/female ratio was 1.2/1; the mean age was 29.2±15.1 (1- 65 years old). The most typical clinical symptoms of the disease are cough (45.8%), fever (45%), stuffy nose (21.7%), anosmia (13.8%), ageusia (12.9%), and shortness of breath (4.6%). Most patients have mild symptoms and a high recovery rate. This study contributes to a general assessment of clinical, subclinical factors, treatment results of COVID-19 patients in general and COVID-19 subjects at the field hospital of Dong Thap Community College in particular, which is the basis for better disease prevention measures. Keywords: COVID-19, clinical features, Ct index, treatment results. References [1] H. A. Rothan, S. N. Byrareddy, The Epidemiology and Pathogenesis of Coronavirus Disease (COVID-19) outbreak, J. Autoimmun, Vol. 109, 2020, https://doi.org/10.1016/j.jaut.2020.102433. [2] D. Cucinotta, WHO Declares COVID-19 a Pandemic, Acta Biomed, Vol. 91, No.1, 2020, pp. 157-160, https://doi.org/10.23750/abm.v91i1.9397. [3] WHO Coronavirus (COVID-19) Dashboard, Global Situation, https://covid19.who.int/ ( accessed on: January 19th, 2022). [4] Y. Xie, Z. Wang, Epidemiologic, Clinical, and Laboratory Findings of the COVID-19 in the Current Pandemic: Systematic Review and Meta-analysis, BMC Infectious Diseases, Vol. 20, 2020, pp. 640, https://doi.org/10.1186/s12879-020-05371-2. [5] T. V. Giang, N. T. Ngoc, Clinical and Subclinical Characteristics of Patients With Pneumonia Cause by COVID-19 Treated at National Hospital of Tropical Diseases, Vietnam Medical Journal, Vol. 509, 2021, pp. 348-351 https://doi.org/10.51298/vmj.v509i1.1770 (in Vietnamese ). [6] W. J. Guan, Clinical Characteristics of Coronavirus Disease 2019 in China, N Engl J Med, Vol. 382, 2020, pp.1708-1720, https://doi.org/10.1016/j.jemermed.2020.04.004. [7] Y. Lee, Prevalence and Duration of Acute Loss of Smell or Taste in COVID-19 Patients, J Korean Med Sci, Vol. 35, No. 18, 2020, pp.174, https://doi.org/10.3346/jkms.2020.35.e174. [8] A. Singanayagam, Duration of Infectiousness and Correlation with RT-PCR Cycle Threshold Values in Cases of COVID-19, England, January to May 2020, Euro Surveill, Vol. 25, No. 32, 2020, https://doi.org/10.2807/1560-7917.ES.2020.25.32. 2001483. [9] A. Jain, Is There a Correlation Between Viral Load and Olfactory & Taste Dysfunction in COVID-19 Patients?, Am J Otolaryngol, Vol. 42, No. 3, 2020, pp.102911, https://doi.org/10.1016/j.amjoto.2021.102911.